Przestrzeń poza kadrem – o sensualnym wymiarze zdjęć filmowych Emmanuela Lubezkiego - Pękala, Iga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The article presents an analysis of the sensual potential of film images via the example of cooperation between operator Emmanuel Lubezki and three directors: Alejandro Gonzales Iñárritu, Alfonso Cuarón and Terrence Malick. The impact of reconstruction of film space on the sensual impressions of viewers in the context of the American theory of somatic cinema was also analyzed. What influence does the dimension of cinematographic cooperation have on the concept of authorial cinema?